ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PINJAMAN LUAR NEGERI PEMERINTAH DAN KAJIAN TAX AMNESTY SEBAGAI PENDAPATAN PEMERINTAH - Nurina, Lia; Napiajo, Napiajo (Jurnal Ekonomi STIEP, 2023)
Indonesia has implemented expansionary economic policies with expenditures exceeding Increasing revenues in an attempt to align with others countries terms of economic development. The government has relied on foreign loans as the main source of financing to support these expenditures. However, Monitoring the utilization is crucial government foreign loans Because it can exert a substantial influence on the nation's economy, this study seeks to examine the determinants that affect the government's policy in taking foreign loans as well as to evaluate the effect of revenue from tax amnesty on Indonesia's foreign loans. This research method uses secondary data covering the period 1987-2021 and analyzes the relationship between several variables, including government spending, interest rates, rupiah exchange rates, inflation, taxes, government securities (SBN), and tax amnesty on government foreign loans. This study uses the ARDL structural break econometric approach. The findings from this research indicate that over the short duration, government spending, exchange rate, taxes, and government securities (SBN), along with related factors, have a significant negative effect on the amount of government foreign loans. On the other hand, bank Indonesia interest rate (BI rate), inflation, and tax amnesty have a significant positive impact to foreign borrowing. However, in the long run, inflation and tax have a significant negative impact, while SBN has a positive impact.